Framework of 5S Quality Management for University Ecosystem to Achieve Green Campus - Abu Bakar, Nashirah; Rosbi, Sofian; Abu Bakar, Azizi; Che Arshad, Noraziah; Abd Aziz, Noriza; Uzaki, Kiyotaka (International Journal of Scientific Research and Management (IJSRM), 2019)
The objective of this paper is to evaluate framework of 5S quality management for university ecosystem to achieve green campus. The main elements in 5S quality management are sort (seiri), set in order (seiton), shine (seiso), standardize (seiketsu), and sustain (shitsuke). The 5S quality improvement method is defined as a methodology that results in a workplace that is clean, uncluttered, safe, and well organized to help reduce waste and optimize productivity. It's designed to help build a quality work environment, both physically and mentally. The function of 5S method is to improve process efficiency and safety, reduces waste, prevents errors and defects. This paper focuses on implementation of 5S in university environment that mainly on areas of education system, finance management, man power arrangement, energy saving operation and building maintenance. In the same time, this paper propose evaluation of green 5S quality management in considering effect to environmental issues. The novelty of this framework is it provides academic institutional about standard operational for implementing quality management that considering environmental issues and efficient procedure for proses in management of university.